Menstrual Phenotypes in Relation to Insulin Resistance in Infertile Women with Polycystic Ovary Syndrome - Ishrat, Shakeela; Hossain, Marufa (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective: To explore the menstrual phenotypes associated with endocrine, metabolic characteristics of infertile women with polycystic ovary syndrome. Materials and methods : The cross sectional study was carried out among 125 infertile women with polycystic ovary syndrome attending Infertility wing of the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2017 to December 2017. The women were evaluated by clinical history, examination, transvaginal sonogram and for endocrine and metabolic parameters. The women were divided into 5 groups according to their menstrual phenotypes: i) cycle length 21-35 days ii) oligomenorrhoea or cycle length > 35 days but less than 6 months iii) secondary amenorrhoea or cycle length ³6 months iv) polymenorrhoea or cycle length <21 days v) oligomenorrhoea alternating with polymenorrhea. One way ANOVA was used for analyzing the variance between groups. Categorical variables were analyzed for association by Fishers Exact Test and Chi Square tests where appropriate. Results: A total of 125 women were recruited for the study. The women were divided into 5 groups according to their menstrual phenotype: i) cycle length 21-35 days (n=5) ii) oligomenorrhoea or cycle length > 35 days but less than 6 months (n=70) iii) secondary amenorrhoea or cycle length ³6 months (n=35) iv) polymenorrhoea or cycle length <21 days (n=2) v) oligomenorrhoea alternating with polymenorrhea (n=13). Accordingly the women with oligomenorroea with or without polymenorroea was most frequent (65%) followed by women with secondary amenorrhea (27%), regular cycle (0.04%) and isolated polymenorroea (0.01%). One way ANOVA revealed significant difference between groups in fasting insulin and serum testosterone level. There is significant association of oligomenorroea (with or without polymenorrhoea) with insulin resistance (HOMA-IR ³2). There is significant association of secondary amenorrhoea with hyperinsulinaemia ( Fasting insulin ³10mIU/L) and insulin resistance (HOMA-IR ³2). Conclusions: Menstrual history of infertile women with polycystic ovary syndrome can be a clinical marker of insulin resistance and related metabolic risk. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 32-36